The Effect Work Culture and Competence on Commitment and Employee Performance of PT. Nindya Karya (Persero) - Bambang Asmoro; Nurdjanah Hamid; Wahda Rasyid (Hasanuddin Journal of Business Strategy, 2020)
The research aimed to determine the effect work culture and competence on commitment and performance employee at PT. Nindya Karya (Persero). The research used quantitative approach by basing the rational principle study. The analysis was carried out using the sem analysis method and processed using SPSS AMOS 26. Data from permanent employees of PT Nindya Karya (Persero) were determined based on proportional sampling. A total of 250 respondents were drawn from 5 branch offices in Indonesia. Data collection uses questionnaires as the main instrument, interviews, and observations. The results showed that: 1) Work culture has a positive and significant effect on employee work commitments at the Office of PT. Nindya Karya (Persero), 2) Work Culture has a positive and significant effect on employee performance at the Office of PT. Nindya Karya (Persero), 3) Competence has a positive and significant effect on employee work commitments at the Office of PT. Nindya Karya (Persero), 4) Competence has a positive and significant effect on employee performance at the Office of PT. Nindya Karya (Persero), 5) Improved work culture will reduce performance through work commitments at the office of PT. Nindya Karya (Persero), 6) Increased competence will reduce performance through work commitments at the office of PT. Nindya Karya (Persero).